Business response to environental challenges: three cases of Russian industrial companies - Oleg Vikhanskiy; Natalia Churkina; Sergey Zaverskiy (Oñati Socio-Legal Series)
Three decades ago environmental protection was perceived by businesses as an additional cost-generating activity, but nowadays the idea that environmental policies can be profit-generating is gaining wider recognition. In Russia the environmental policy of many companies still follows the old “end-of-pipe” paradigm. However, changes in national government regulations, shifts in public opinion and international environmental initiatives force some companies to change their attitude to environment protection. Our study is focused on an analysis of environmental policies of three Russian companies: UC RUSAL, world leader in aluminum production, GAZ Group, the largest vehicle producer in Russia, and Baikalsk TsBK, a pulp and paper producer. We examine the development of environmental responsibility within these companies and the relationship between their business goals and environment protection tasks. We reveal the positive and negative effects of environmental activities and the problems the companies face while developing and implementing their environmental policies. On the basis of these cases we suggest government policy implications for emerging economies, which must include a change in priorities – from imposing penalties and environmental payments to creating new incentives for business on the basis of private-public partnerships.